1998
DOI: 10.1359/jbmr.1998.13.12.1932
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Falls and Fractures in the Longitudinal Aging Study Amsterdam

Abstract: The objective of this study was to identify easily measurable predictors for falls, recurrent falls, and fractures using a population-based prospective cohort study of 1469 elderly, born before 1931, in three regions of the Netherlands. The baseline at-home interview was in 1992. In 1995, falls experienced in the preceding year and fractures over the preceding 38-month period were registered. In a period of 1 year, 32% of the participants fell at least once, and 15% fell two or more times. The rate of recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
177
4
10

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(203 citation statements)
references
References 38 publications
11
177
4
10
Order By: Relevance
“…Our study assessed both genders of the general population aged 40 and older. The prevalence was similar to that found in the Study of Osteoporotic Fractures (SOF) 14 , LASA 15 and a study carried out in southern Australia, in which 28 to 32% of individuals reported at least one fall in the previous year 16 . In Latin America, the prevalence of falls also exhibits considerable variation (from 21.6% in Barbados to 34% in Chile).…”
Section: Discussionsupporting
confidence: 85%
“…Our study assessed both genders of the general population aged 40 and older. The prevalence was similar to that found in the Study of Osteoporotic Fractures (SOF) 14 , LASA 15 and a study carried out in southern Australia, in which 28 to 32% of individuals reported at least one fall in the previous year 16 . In Latin America, the prevalence of falls also exhibits considerable variation (from 21.6% in Barbados to 34% in Chile).…”
Section: Discussionsupporting
confidence: 85%
“…In previous studies in the LASA cohort and in other studies, poor balance was a risk factor for falls [7,26], which cause more than 90% of hip fractures [27]. In addition to balance, functional status and other measures of physical performance were also risk factors for falls [7,28]. Moreover, functional status and physical performance can be improved by training [29], and these risk factors may therefore be valuable for intervention strategies.…”
Section: Discussionmentioning
confidence: 96%
“…The predictive value of the tandem stand might be better if the tandem stand is assessed for more than 10 s [25]. In previous studies in the LASA cohort and in other studies, poor balance was a risk factor for falls [7,26], which cause more than 90% of hip fractures [27]. In addition to balance, functional status and other measures of physical performance were also risk factors for falls [7,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have considered fractures that occur as a result of any fall from a height of less than a meter, such as after having missed 1 to 3 steps in a staircase, as fragility fractures. [50][51][52][53][54][55] Measurement of height loss is a good clinical indicator of vertebral fracture. 56 Klotzbuecher et al 57 performed a meta-analysis of the risk of future fracture, given the history of prior fracture, and concluded that women with prior fracture had a 2-to 10-fold risk of another fracture, compared with those without fracture.…”
Section: Women At Risk Of Fragility Fracturementioning
confidence: 99%